2019
DOI: 10.1167/tvst.8.6.29
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Transmembrane Protein 119 in the Retina is Not Restricted to the Microglia: An Immunohistochemical Study

Abstract: Purpose: Recently, a new marker protein for microglial cells in the brain was postulated, transmembrane protein 119 (TMEM119), raising the hope for a new opportunity to reliably and unambiguously detect microglial cells in histologic sections. It was of interest whether TMEM119 also was a reliable microglial marker in the retina.Methods: Anti-TMEM119 antibodies of two providers were used to label microglia in the murine retina, and labeling properties were compared to those of antibodies against Iba1 and CD11b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Increasing evidence has revealed that the activation patterns of MGs in response to HI differ throughout development (Cengiz et al, 2019 ). However, CD11b + cells are traditionally regarded as MGs even though both MGs and MDMs express CD11b (Denker et al, 2007 ; Su et al, 2019 ; Nishihara et al, 2020 ). Due to a lack of specific discriminating cell markers, an open challenge is to properly characterize the roles of MGs and MDMs in neonatal brain HI injury progression and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that the activation patterns of MGs in response to HI differ throughout development (Cengiz et al, 2019 ). However, CD11b + cells are traditionally regarded as MGs even though both MGs and MDMs express CD11b (Denker et al, 2007 ; Su et al, 2019 ; Nishihara et al, 2020 ). Due to a lack of specific discriminating cell markers, an open challenge is to properly characterize the roles of MGs and MDMs in neonatal brain HI injury progression and resolution.…”
Section: Introductionmentioning
confidence: 99%
“… 63 , 64 Proposed new markers from RNA sequencing studies such as transmembrane protein 119 (TMEM119) have been recently challenged on their specificity (e.g., in the retina). 65 On the other hand, the retina provides a unique opportunity to explore novel viral transduction strategies and validating new promoters in future studies. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Later, Bennett and colleagues (2016) showed that both mouse and human microglia cells generate Tmem119 protein for which no expression in peripheral myeloid cells was detected [105]. Yet, another group has shown that the expression of this protein was not restricted to microglia cells [106]. Butovsky et al (2014) showed that antibodies produced against P2ry12 and FCRLS proteins could make a difference between microglia and infiltrating myeloid cells [107].…”
Section: Immunolabelingmentioning
confidence: 99%